History and status of the population dynamics of moose in the steppe zone of Ukraine - Volokh, Anatolii; Волох, Анатолій Михайлович; Волох, Анатолий Михайлович (My University, 2009)
The moose (Alces alces) population in the steppe zone of Ukraine developed initially in 1955-1965. Early annual population growth rates were high ranging from 13-49% partly due to immigration of moose from Russia and Byelorussia. However, after fully occupying forest habitat and expanding to treeless biotopes, reproductive efficiency declined. This decline was influenced by large spatial isolation of suitable habitat; 52% of solitary males and 48% of solitary females were in isolated biotopes during breeding. Further, 8% of adult bulls were in herds without cows, and 21% of cows were in herds without bulls. Although individual productivity was good, 1.3±0.1/pregnant cow and 0.4/adult cow, isolation caused low participation in breeding (38.5% of adult cows), low number of calves (17.1% of population), and low annual population growth rate (≈ 6%/yr). The steppe moose population reached its maximum (n = 2776) in 1974 followed by steep decline; the decline was associated with harvests of 16.1% in 1973 and 12.5% in 1974, of which about 50% were adult animals. The population reached a second peak (n = 2147) in 1982 and declined gradually until 1992. A steep, annual population decline of 25.3±5.8% occurred after 1992; this decline was associated with excessive harvest beyond the annual population growth rate. Moose were extirpated from most regions of the steppe zone by the late 20th century. The current southern range of moose is limited to forest habitat, and except for a remnant population of about 80, the unique steppe population has disappeared from Ukraine.
Keywords: Alces alces; biotopes; dynamics; hunting; moose; population; steppe zone; structure Ukraine